Aftermath : life in the fallout of the Third Reich, 1945-1955 - Jähner, Harald, 1953- (Alfred A. Knopf, 2022)
"A revelatory history of the transformational decade after World War II when Germany raised itself out of the ashes of defeat, turned away from fascism, and reckoned with the corruption of its soul, and the horrors of the Holocaust"--